'Naked-eye' colorimetric/fluorimetric detection of F− ions by biologically active 3-((1H-indol-3-yl)methyl)-4-hydroxy-2H-chromen-2-one derivatives. Issue 109 (14th November 2016) - Shaily,; Kumar, Ajay; Kumar, Sumit; Ahmed, Naseem
Abstract : An improved synthetic protocol has been developed to construct highly functionalized heterologous alkyl and benzyl indolyl-coumarin derivatives using a rapid, catalyst-free and solvent-free one-pot three-component reaction of indole, aldehyde and 4-hydroxy-coumarin. Abstract : An improved synthetic protocol has been developed for the construction of highly functionalized heterologous alkyl and benzyl indolyl-coumarin derivatives through a rapid, catalyst-free and solvent-free one-pot three-component reaction of indole, aldehyde and 4-hydroxycoumarin. The synthesized compounds display a high selectivity and sensitivity towards F − ions. The detection of F − ions was accompanied by fluorescence quenching with noticeable colour change, which is evident from the Stern–Volmer plot. The Stern–Volmer plot shows an association constant of 6.2625 × 10 4 M −1 with a lowest detection limit (LOD) of 0.50 μM for F − ions. The interaction mechanism was studied by 1 H-NMR titration and also supported by advanced TD-DFT calculations. The designed chemosensor has been utilized as a mini colorimetric kit for F − ions on test paper strips and is also capable of detecting F − ions in commercially available toothpaste and mouth rinser. The chemosensors also exhibited good antifungal and antibacterial activity.